Where everybody knows your name: Adolescent well-being and relationships in smaller and larger settlements - Rúnarsdóttir, Eyrún María (Félagsfræðingafélag Íslands, 2023)
International research present conflicting findings on whether well-being is better supported in rural or urban environments, but this aspect remains unexplored in the context of Iceland. The study aimed to assess and compare psychosomatic complaints among adolescents between urban and semi-urban areas. Additionally, the research explores the influence of gender, age, family affluence, and the number of friends on adolescent well-being. A survey was conducted across nine schools, with four in the capital area, two in Reykjanes, and three in the western and northern regions of the country, involving 806 participants ranging from 8th to 10th graders. The findings revealed a higher prevalence of psychosomatic complaints among adolescents in the capital area compared to other regions. Girls reported more complaints than boys, and older adolescents more than their younger counterparts. Furthermore, lower family affluence was associated with a higher frequency of complaints. While a positive correlation was observed between more frequent complaints and a higher number of internet friends, interaction revealed that internet friendships appeared to benefit adolescents in the West and North more than their counterparts in the capital area. The findings underscore the significance of considering adolescent’s social settings when formulating interventions to improve their well-being. Lífsgæði og versnandi líðan unglinga hefur verið skoðuð í samhengi samfélagsbreytinga en búsetuskilyrði hafa lítið komið við sögu í þeirri umræðu. Erlendar rannsóknir sýna misvísandi niðurstöður um það hvort unglingum í borgum eða strjálli byggð líður betur en líðan unglinga eftir byggðasvæðum hefur ekki verið könnuð hérlendis. Markmið rannsóknarinnar var að bera saman tíðni sállíkamlegra umkvartana unglinga eftir byggðalögum. Einnig var horft til kyns, aldurs, efnahags fjölskyldu og fjölda vina í tengslum við líðan. Spurningalisti var lagður fyrir nemendur í 8.–10. bekk í níu grunnskólum. Þar af voru fjórir skólar á höfuðborgarsvæðinu, ...